The Interplay of Partner Support and History of Anxiety in the Etiology of Postpartum Depression: A Systematic Review - Irma Gama Setyarini; Andy Soemara (The International Journal of Medical Science and Health Research, 2025)
Introduction: Postpartum depression (PPD) is a significant global health concern with detrimental effects on maternal, infant, and family well-being. While its etiology is multifactorial, a history of anxiety and the quality of partner support have emerged as two of the most critical psychosocial predictors. This systematic review aims to synthesize quantitative evidence on the individual and combined associations of partner support and history of anxiety with the development of PPD. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases was conducted for quantitative observational studies published from 2004 to 2024. Studies were included if they assessed postpartum depressive symptoms as an outcome and included measures of both partner support (or a related construct) and anxiety. Data on study design, sample characteristics, measurement tools, and key quantitative findings were extracted. The methodological quality of included studies was assessed using the Newcastle-Ottawa Scale. Results: Sixteen studies, comprising cross-sectional and longitudinal cohort designs, met the inclusion criteria. The evidence consistently demonstrated that inadequate or negative partner support (e.g., low satisfaction, high conflict, intimate partner violence) and a history of anxiety (both antenatal and trait anxiety) are strong, independent predictors of higher PPD symptom severity. Low partner support was associated with significantly increased odds of PPD, while antenatal anxiety was a robust predictor of subsequent PPD. Furthermore, evidence suggests an interactive relationship, where poor partner support is also linked to increased perinatal anxiety, creating a pathway that elevates PPD risk. Discussion: The findings support a biopsychosocial model where anxiety may confer a biological and psychological vulnerability to PPD, which is either exacerbated by poor partner support or buffered by a positive, supportive relationship. The high comorbidity of anxiety and PPD, coupled with the influence of the partner relationship, suggests that these conditions often manifest in a syndemic fashion. This underscores the need for a paradigm shift in perinatal care from an individual, mother-centric model to a dyadic, family-centered approach. Conclusion: Partner support and a history of anxiety are pivotal factors in the etiology of PPD. Clinical practice should incorporate integrated screening for both anxiety and relationship quality during the perinatal period. Future research should prioritize longitudinal, dyadic studies to further elucidate causal pathways and test the efficacy of partner-inclusive preventative interventions.